Intracameral air injection after completion of phacoemulsification cataract surgery: Evaluation of corneal incisions with optical coherence tomography - Çubuk, Mehmet Özgür; Yüksel, Erdem; Serbest Ceylanoğlu, Kübra (Medknow, 2019)
To evaluate the effects of air bubbles on clear corneal incision (CCI) in patients who had phacoemulsification surgery, and to compare this type of CCI architecture with patients who had no air bubbles after phacoemulsification surgery, using anterior segment optical coherence tomography (AS-OCT).Eyes which had undergone uneventful phacoemulsification cataract surgery with implantation of a posterior chamber intraocular lens (IOL) were equally randomized into two groups. Group 1 comprised patients with anterior chamber air bubble injection after phacoemulsification, and Group 2 comprised patients who had undergone phacoemulsification surgery without anterior chamber air bubble. Postoperative evaluation included AS-OCT (Heidelberg Engineering, Germany) and pneumatic tonometry (Nidek NT-1000 Pneumatic Tonometer, Japan) in the 2nd hour, then at 1 week, and 1 month. Astigmatic changes assessed with corneal topography after phacoemulsification cataract surgeries were noted.Evaluation was made of 40 eyes of 28 patients (10 female, 18 male) as 20 eyes in Group 1 and 20 eyes in Group 2. On the first postoperative day, the endothelial gap rate was 13.3% in Group 1 and 57.1% in Group 2 (P = 0.02), and this continued until the 1-month follow-up examination. The Descemet's membrane detachment (DMD) rate was 0% in Group 1 and 42.8% in Group 2 on postoperative day 1 (P = 0.006), and this continued at the 1-month follow-up examination. At 1 month postoperatively, the rates of optical coherence tomography (OCT) parameters were similar. There were no significant differences between preoperative astigmatism and postoperative astigmatism in the group analyses.In this study, air bubbles decreased the rate of DMD and of endothelial and epithelial gap during the early postoperative period.
Keywords: Ophthalmology; RE1-994; Article